Totally real submanifolds of a complex space form - U-Hang Ki; Young Ho Kim (International Journal of Mathematics and Mathematical Sciences)
Totally real submanifolds of a complex space form are studied. In particular, totally real submanifolds of a complex number space with parallel mean curvature vector are classified.